1983
DOI: 10.2224/sbp.1983.11.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Unbiasing the Brain: The Effects of Meditation Upon the Cerebral Hemispheres

Abstract: Twenty males with a strong right hand preference underwent 120 simple reaction time trials to a 500 hz auditory stimulus presented to right, left and both ears. Ten Transcendental Meditators served as their own controls in twenty minute meditation and relaxation conditions and were also compared to a ten Non-Meditator control group who relaxed only in two 20-minute conditions. The reaction time trials were administered after the conditions. When the ears were compared to each other a significant right-ear (le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…Thus, at least in the aspects measured by our procedure, Transcendental Meditators do not appear to be more lateralized than nonmeditators, contrary to the EEG results of Bennett and Trinder (1977). Nor are they less lateralized than nonmeditators, as suggested by the ear-superiority data of Meissner and Pirot (1983).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Thus, at least in the aspects measured by our procedure, Transcendental Meditators do not appear to be more lateralized than nonmeditators, contrary to the EEG results of Bennett and Trinder (1977). Nor are they less lateralized than nonmeditators, as suggested by the ear-superiority data of Meissner and Pirot (1983).…”
Section: Discussioncontrasting
confidence: 56%
“…Others interpreted these results as support for meditation's causing improved alertness outside of the meditative state (Dillbeck & Orme-Johnson, 1987, p. 880), presumably because of better flexibility to use the hemisphere appropriate to any given task. Meissner and Pirot (1983) also showed persistent effects of meditation, but in the direction of reducing asymmetry, thus contradicting Bennett and Trinder. Their measure also differed: Instead of using EEG, they tested left-versus right -ear superiority for recognition of tones.…”
Section: No Difference In Cerebral Hemispheric Asymmetry Of Meditatormentioning
confidence: 79%
See 1 more Smart Citation
“…A similar rationale is used by people who advocate meditation as a counseling intervention. Meissner and Pirot (1983), for instance, conducted a study to assess the effects of transcendental meditation on the perceptual efficiency of cerebral hemispheres. They found that after meditation, participants responded-more slowly to information presented auditorially to the left hemisphere.…”
Section: Counseling Strategiesmentioning
confidence: 99%